A STUDY ON GREEN ECONOMY AND SUSTAINABLE DEVELOPMENT - Tanmoy Samanta (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This literature review identifies the impacts on habitats and biodiversity of different renewable energy pathways and their consequences for a green economy transformation. While greater renewable energy penetration is at present the basis of Green Economy initiatives, emerging literature shows that the renewable energy sector will impact ecosystems and biodiversity. The existing analysis synthesises existing information within the Millennium Ecosystem Assessment system loss/change habitats, emissions, over-exploitation, climate change, introducing invasive species) at a relationship between renewable energies and biodiversity within five drivers of evolving ecosystems and biodiversity loss. It identifies critical mechanisms for different pathways, including solar, wind, hydro, oceans, energy, and bioenergy, for renewable energy. Our analysis shows that while each of the five drivers of ecological change and biodiversity losses is related directly or indirectly, the exact mechanisms for impacts are significantly dependent on the different pathways, particular technologies, and environmental contexts within them. This analysis does not challenge the basic logic of renewable energy expansion since the socio-economic and ecological benefits are high. However, we should point out that there are such adverse effects on biological diversity and that they must be taken into account in designing policies on renewable energy. We put this finding into context by showing the significant differences and policy consequences in awareness/practice at the intersection of renewable energy, biodiversity conservation, and the green economy.